PHYTOPLANKTON ABUNDANCE VARIATION AT FLOATING NET CAGE AREA, JATILUHUR RESERVOIR, WEST JAVA - Masayu Rahmia Anwar Putri; Sri Endah Purnamaningtyas (Pusbindiklat - LIPI, 2013)
Eutrophic waters are one triggering factor for the explosion of harmful phytoplankton populations. The aim of this study is to determine the abundance of phytoplankton in floating net cage area Jatiluhur Reservoir. Research carried out in January and March of 2009 and 2010. Water sample taken vertically by water depth, and taken temporally based on the observation time. The composition of phytoplankton and it is abundance in 2010 in Jatiluhur Reservoir less than 2009. 48–49 genus of phytoplankton found on 2009 and on 2010, just 20–25 species found. Based on its composition Chlorophyceae class more than others and based on its abundance, the Cyanophyceae class more dominated. The composition and the abundance of phytoplankton have a different pattern in every observation time and also changed by its depth. The highest of Cyanophyceae class indicated that Jatiluhur reservoir was eutrophic waters.